2014
DOI: 10.1103/physrevlett.112.135503
|View full text |Cite
|
Sign up to set email alerts
|

Steering of a Sub-GeV Electron Beam through Planar Channeling Enhanced by Rechanneling

Abstract: We report the observation of efficient steering of a 855 MeV electron beam at MAMI (MAinzer MIkrotron) facilities by means of planar channeling and volume reflection in a bent silicon crystal. A 30.5  μm thick plate of (211) oriented Si was bent to cause quasimosaic deformation of the (111) crystallographic planes, which were used for coherent interaction with the electron beam. The experimental results are analogous to those recorded some years ago at energy higher than 100 GeV, which is the only comparable s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
111
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(122 citation statements)
references
References 41 publications
8
111
2
1
Order By: Relevance
“…The standard deviation of the distribution matches the experimental value of 0.1 mrad. Thus, two thousand mrad which is comparable to that for planar channeling in bent crystals [6,7] because the critical angle increases at lower energies. The fraction of deflected particles calculated by Gaussian gives 29% [14].…”
Section: Experimental Results and Simulationsmentioning
confidence: 75%
See 1 more Smart Citation
“…The standard deviation of the distribution matches the experimental value of 0.1 mrad. Thus, two thousand mrad which is comparable to that for planar channeling in bent crystals [6,7] because the critical angle increases at lower energies. The fraction of deflected particles calculated by Gaussian gives 29% [14].…”
Section: Experimental Results and Simulationsmentioning
confidence: 75%
“…These early studies have been carried out using positively charged particles. Recently, these techniques has been proven to be useful even for negatively charged particles -relativistic electrons -at MAMI (855 MeV [6]) and at SLAC (3.35 and 6.3 GeV [7]). These experiments showed that there appear a large deflection angle in the channeling orientation and a smaller one in the volume-reflection orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Under the planar channeling condition [1,2], during transmission of energetic particles through crystal planes in the harmonic (oscillator potential) approximation, effect of coherence can be established under circumstances of phase summation, which depend on the periodical arrangement of the crystal atoms at selected beam parameters. Planar oscillations are induced by the interacting potential U pl (p), which is experienced by the energetic particle as a sum of the potentials generated by the strong electromagnetic field between crystal planes where the channeled oscillations occur.…”
Section: Introductionmentioning
confidence: 99%
“…For negatively charged particles, since the minimum of the potential well is located on the atomic planes, the mechanism of electronic de-channeling has a negligible contribution ( f e ∼ 0, f n ∼ 1) because all the particles do interact with nuclei [5,6,26]. Therefore, the channeled-particle fraction f ch,− holds,…”
mentioning
confidence: 99%
“…Measurements proved the capability of channeling for manipulation of positively [4] and negatively [5,6] charged particle beams from MeV [7] up to hundreds of GeV [8,9], and for the generation of intense electromagnetic radiation from sub-GeV [10,11] to hundreds-GeV electron beams [12]. Moreover, channeling effects were exploited for steering [13], collimation [14] and extraction [15] of relativistic beams in circular accelerators, as well as splitting and focusing of extracted beams [16], a e-mail: bagli@fe.infn.it leading to the installation of two bent crystals in the Large Hadron Collider (LHC) for collimation purposes [17].…”
mentioning
confidence: 99%